Bibliometric analyses of publications from Centres of Excellence funded by the Danish National Research Foundation - Schneider, Jesper Wiborg; Costas, Rodrigo (CFA Scientific Reports, 2013)
Since 1993 the Danish National Research Foundation (DNRF) has funded Centres of Excellence (CoE) in Denmark. Scientific excellence is demanded from candidates, hence the selection process is hard, rejection rates high, but the eventual funding of the CoEs is very large and long-termed - up to 10 years - compared to other funding instruments. These conditions represent a unique setting for CoEs for doing outstanding research. In that respect, DNRF as a funding organization is being evaluated and the present report supplements this evaluation by investigating the overall performance of research publications coming from CoEs funded by DNRF. To the extent that citations can somehow be considered a proxy for ‘research quality’ or rather impact in the scientific community, the goal of providing unique settings for producing outstanding research ought therefore to result in relatively high citation indicators, if indeed such outstanding research is produced. The main purpose of this report is to investigate this question.